1996
DOI: 10.1021/jp961044q
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Si and Al Distributions in Molecules and Minerals with Eight Tetrahedrally Coordinated Atoms (T8) in Double-Four-Ring (D4R) Geometries:  Octasilasesquioxanes, Gismondite, and Zeolite A

Abstract: The inorganic compound octasilasesquioxane, Si 8 O 12 H 8 , the mineral gismondite, CaSi 2 Al 2 O 8 ‚4H 2 O, and synthetic Linde zeolite A all contain structural units in which eight tetrahedrally coordinated atoms (T 8 , T ) Si and/or Al) and their bridging oxygens form a double-four-ring (D4R) geometry. D4R compounds are much more stable than the single four rings that occur in some crystalline silicates and silicate glasses, since hydrolysis by nucleophilic attack at the T-atom is hindered by the cage geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…The reactant molecule Si 4 Al 4 O 12 H 8 Na 4 is of C 4 v symmetry with the Na + ions on the outsides of four faces of the T 8 cube. This molecule is shown in Figure of ref (identified as Si 4 Al 4 O 12 H 8 Na 4 , Al···Si···Al···Si), and its structure agrees well with experiment, as discussed in ref .…”
Section: Resultssupporting
confidence: 85%
“…The reactant molecule Si 4 Al 4 O 12 H 8 Na 4 is of C 4 v symmetry with the Na + ions on the outsides of four faces of the T 8 cube. This molecule is shown in Figure of ref (identified as Si 4 Al 4 O 12 H 8 Na 4 , Al···Si···Al···Si), and its structure agrees well with experiment, as discussed in ref .…”
Section: Resultssupporting
confidence: 85%
“…Significant shifts of the vibrational frequencies may be observed. 23 The introduction of balancing point charges may prevent correct geometry optimization. Different Si,Al distributions in D6R's were examined in order to compare the gasphase ion-exchange energies: clusters with C 2h symmetry have with maximum separation of the Al atoms within the ring were used to examine the SII sitesin the case of monovalent cations, the clusters were negatively charged.…”
Section: Methodsmentioning
confidence: 99%
“…They are discussed as oligomeric supramolecular materials, , as sources for new organosiliceous polymers, , and as precursors to organolithic macromolecular materials (OMM's) or hybrid inorganic−organic materials. Moreover, it has been shown that atomic hydrogen can be encapsulated stably in the Si 8 O 12 cage . Hydrosilasesquioxanes (R = H) have been fruitfully viewed as readily available model compounds for studying specific aspects of zeolites or silica surfaces. Especially H 8 Si 8 O 12 has been thoroughly investigated by X-ray and neutron diffraction, , as well as NMR and vibrational spectroscopies. , Hydrosilation of H 8 Si 8 O 12 leads to monosubstituted and higher substituted octanuclear silasesquioxanes, which can be separated by size exclusion liquid chromatography . The compounds RH 7 Si 8 O 12 with R = Co(CO) 4 , CHCHPh, and CH 2 CH 2 Ph illustrated in Scheme have been synthesized by this method. , PhH 7 Si 8 O 12 in contrast was obtained starting from a mixture of HSiCl 3 and PhSiCl 3 …”
Section: Introductionmentioning
confidence: 99%